Organizational Support Factors for Minor League Baseball Player Development - Christopher McLeod; Nola Agha; Simon Rosenblum-Larson (Bowling Green State University, 2022)
This study examines organizational support in the context of minor league baseball to better understand how organizations can support athletes' development. Exploratory results show that English and Spanish players identify salary/pay, off-season training opportunities, and nutritious food as their most important unmet development needs. English and Spanish respondents differently prioritized playing opportunities, communication with front office staff, health care, and equipment as unmet needs. Explanatory results show that organizational support factors (private problem support and second career support) explain 17% of the variation in minor league baseball players' self-perceptions of development. The results provide guidance for Major League Baseball and its affiliates as they restructure the development system and for non-profits seeking to help players. Better pay and other financial support appear to be the most critical unmet needs where organizations can better support athletes.